2002
DOI: 10.1046/j.1365-2958.2002.02742.x
|View full text |Cite
|
Sign up to set email alerts
|

A maize‐specifically expressed gene cluster in Ustilago maydis

Abstract: Summary The corn pathogen Ustilago maydis requires its host plant maize for development and completion of its sexual cycle. We have identified the fungal mig2–1 gene as being specifically expressed during this biotrophic stage. Intriguingly, mig2–1 is part of a gene cluster comprising five highly homologous and similarly regulated genes designated mig2–1 to mig2–5. Deletion analysis of the mig2–1 promoter provides evidence for negative and positive regulation. The predicted polypeptides of all five genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 49 publications
0
74
0
2
Order By: Relevance
“…The largest class of U. hordei effectors contained 19 Mig1-related proteins having a characteristic and conserved pattern of Cys residues. In U. maydis, Mig1 was shown to be highly induced during biotrophic growth in maize (Basse et al, 2002). U. maydis has only three copies of Mig1-like genes, while eight copies exist in S. reilianum (see Supplemental Figure 10 online; Schirawski et al, 2010).…”
Section: Csepsmentioning
confidence: 99%
“…The largest class of U. hordei effectors contained 19 Mig1-related proteins having a characteristic and conserved pattern of Cys residues. In U. maydis, Mig1 was shown to be highly induced during biotrophic growth in maize (Basse et al, 2002). U. maydis has only three copies of Mig1-like genes, while eight copies exist in S. reilianum (see Supplemental Figure 10 online; Schirawski et al, 2010).…”
Section: Csepsmentioning
confidence: 99%
“…The ip gene (Broomfield and Hargreaves, 1992) is constitutively expressed and allows quantification of the overall presence of the fungus. Expression of mig2-5, which is strictly linked to biotrophic growth (Basse et al, 2002a), provides for a suitable marker for the fungal presence within plant tissue. Transcript levels of mig2-5 were comparable in samples T1 and T3 were reduced in sample T2 and lowest in T4 (Fig.…”
Section: Expression Of Umi Genes In Dependence On Tumor Formation Andmentioning
confidence: 99%
“…Gene-specific primer combinations were used to determine expression of mig2-5 (m25gsa/m25gsb; Basse et al, 2002a) and Umi2 (5#-CCATATCTCACTAC-CAAAAGCATCCGATCC-3#/5#-GTTCCAACCCTTCGAAAAAGTGGTGCG-3#). The primers designed against the Umi2 sequence did not match the sequence of the homologous TPS5 gene.…”
Section: Rt-pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For Avr9 and Mpg1 it was shown that expression (partly) depends on a general nitrogen response factors (NRF1 and NPR1, respectively) (Lau and Hamer, 1996;Perez-Garcia et al, 2001;Soanes et al, 2002). However, expression of other in planta induced genes does not respond to changes in nitrogen availability, for example AVR4, ECP1 and ECP2 (C. fulvum), AvrLm1 (Leptosphaeria maculans), MIG1 and the MIG2 gene cluster (Ustilago maydis) (Basse et al, 2002(Basse et al, , 2000Gout et al, 2006;Van den Ackerveken et al, 1994;Wubben et al, 1994). Even for the genes that are expressed in an environment with limited nitrogen, it is not known which circumstances induce expression in planta, since there are indications that within the host plant, nitrogen is not limiting Oliver, 2001, 2002).…”
Section: Introductionmentioning
confidence: 99%